The Effectiveness of HERO Training to Improve the Engagement of Disaster Volunteers - Erlyani, Neka; Zwagery, Rika Vira; Mayangsari, Marina Dwi (International Journal Labs, 2021)
The future development of CCeU ULM needs to consider the nature of volunteers who do not want to continue to be in the organization. Therefore, retaining volunteers to continue to be actively involved and contribute to the organization is a challenge in itself. This study aims to empirically test the